SDF-1 peptide tethered polyester facilitates tissue repair by endogenous cell mobilization and recruitment - Shafiq, Muhammad; Kong, Deling; Kim, Soo Hyun (WILEY, 2017)
The design of bioactive scaffolds that can invoke host's own regenerative capabilities and facilitate endogenous tissue repair hold great promise. This study aims to evaluate the potential of stromal cell-derived factor 1 alpha (SDF-1)-derived peptide and heparin tethered poly(L-lactide-co-epsilon-caprolactone) (PLCL) copolymers for blood vessel regeneration applications. Amino acid analysis and toluidine blue assays confirm successful conjugation of SDF-1 peptide and heparin with the PLCL copolymers. Assessment of biocompatibility after subcutaneous implantation in rats discloses higher cell infiltration in SDF-1 peptide (SDF-1 group) or SDF-1 peptide and heparin (SDF-1/heparin group) than the control group. SDF-1 and SDF-1/heparin grafts also show more numbers of laminin(+) blood vessels, CD90(+) stem cells, and alpha smooth muscle actin(+) cells than the control group. However, SDF-1 and SDF-1/heparin groups did not significantly differ in terms of blood vessel regeneration and stem cell recruitment. Evaluation of the inflammatory response reveal less numbers of CD68(+) macrophages in SDF-1 and SDF-1/heparin groups compared with the control group; whereas three groups show similar numbers of CD206(+) macrophages. These results indicate that completely synthetic, cell-free grafts can attract endogenous cells and enhance tissue repair. Bioactive polyesters can be fabricated into different shapes and structures for various tissue engineering applications. (c) 2017 Wiley Periodicals, Inc. J Biomater Res Part A: 105A: 2670-2684, 2017
Keywords: ENGINEERED VASCULAR GRAFTS; BLOOD-VESSELS; COVALENT IMMOBILIZATION; LOCAL-DELIVERY; GROWTH-FACTOR; REGENERATION; HEPARIN; POLY(L-LACTIDE-CO-EPSILON-CAPROLACTONE); SCAFFOLDS; ENDOTHELIALIZATION